The influence of cafe atmosphere, food quality and product variety on revisit intention with customer satisfaction as a mediation variable in CW Coffee West Kalimantan - Alessandro, Muhammad Jerry; Syahbandi, Syahbandi; Listiana, Erna; Barkah, Barkah; Rosnani, Titik (Institute of Computer Science (IOCS), 2024)
This research examines the influence of cafe atmosphere, food quality, and product variety on revisit intention, with customer satisfaction as a mediating variable at CW Coffee West Kalimantan. Coffee is a drink that is highly sought after and consumed throughout the world. In 2020, total coffee consumption throughout the world is estimated to reach around 167 million kg. In Indonesia, data shows an increasing trend in coffee consumption, with significant growth over the last seven years, having an impact on the growth of the coffee industry in this country. One of the striking coffee shops in West Kalimantan is CW Coffee. The popularity graph shows that CW Coffee dominates compared to other competitors. CW Coffee is a local brand that started in Pontianak City, and has developed in the West Kalimantan area. In the face of increasingly fierce competition in this industry, this research aims to understand the factors that influence revisit intention at CW Coffee. Several factors that can influence revisit intention include cafe atmosphere, food quality, product variety, and customer satisfaction. In this case, customer satisfaction is considered as a mediating factor that connects these factors with revisit intention. This research uses quantitative methods and focuses on cause-and-effect relationships between variables. Data was collected through a questionnaire with a 5 point likert scale, and the research sample consisted of 220 respondents who were CW Coffee consumers. Data analysis uses Structural Equation Modeling (SEM) with AMOS 24 statistical tools. The results of this research are expected to provide deeper insight into the factors that influence consumers repurchase intentions at CW Coffee, which in turn can help companies improve their marketing strategies and service to customers.